Output Monomial Reachability and Zero Output Controllability of Positive Switched Systems - Maryam Riouali; Fouad Lahmidi; Abdelwahed Namir (International Journal of Mathematics and Mathematical Sciences)
In this paper, we present a sufficient condition for the output reachability of discrete-time positive switched systems. Besides, necessary and sufficient conditions for output monomial reachability and zero output controllability are provided. Further, some examples are shown.